2006
DOI: 10.4141/p05-008
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of multiple herbicide resistance in wild oat (Avena fatua L.)

Abstract: . 2006. Inheritance of multiple herbicide resistance in wild oat (Avena fatua L.). Can. J. Plant Sci. 86: 317-329. To gain some insight into the surprisingly frequent occurrence of multiple herbicide resistant wild oat in western Canada, the inheritance of multiple herbicide resistance was studied in two wild oat (Avena fatua L.) populations, UMWO12-01 and UMWO12-03, from Manitoba, Canada. Both populations are resistant to each of three distinct herbicides, imazamethabenz-methyl, flamprop-methyl, and fenoxapro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…By the mid-1990s, intergroup-resistant populations Á ACC inhibitor, e.g., fenoxaprop,'ALS inhibitor (group 2), e.g., imazamethabenz,'flamprop (group 25)-resistant populations were confirmed in northwestern Manitoba (Friesen et al 2000). In a study of two such populations, a single dominant or semidominant nuclear gene controlled resistance to each herbicide with possible linkage between the genes (Karlowsky et al 2006).…”
Section: (A) Herbicide Resistancementioning
confidence: 99%
“…By the mid-1990s, intergroup-resistant populations Á ACC inhibitor, e.g., fenoxaprop,'ALS inhibitor (group 2), e.g., imazamethabenz,'flamprop (group 25)-resistant populations were confirmed in northwestern Manitoba (Friesen et al 2000). In a study of two such populations, a single dominant or semidominant nuclear gene controlled resistance to each herbicide with possible linkage between the genes (Karlowsky et al 2006).…”
Section: (A) Herbicide Resistancementioning
confidence: 99%
“…Eighteen percent of group 1-HR populations exhibited group 2 resistance, even though group 2 herbicides had not been applied frequently in those fields. Linkage between genes for resistance to herbicides of differing site of action or enhanced metabolism may explain how wild oat populations evolved intergroup resistance in the absence of selection by non-group-1 herbicides (Beckie et al 1999b;Karlowsky et al 2006). The distribution and abundance of group 1-HR wild oat reflected past group 1 herbicide use across ecoregions.…”
mentioning
confidence: 99%
“…Furthermore, genes conferring resistance to imazamethabenz and flamprop‐M‐methyl were linked. However, the physiological mechanisms conferring MHR in UMWO12‐01 and UMWO12‐03 are unknown (Karlowsky, ), in contrast to the MHR3 and MHR4 A. fatua populations discussed here. However, as TSR is generally much more prevalent than NTSR (Heap, ), it seems likely that resistance in UMWO12‐01 and UMWO12‐03 is due to TSR.…”
Section: Discussionmentioning
confidence: 88%
“…Our findings are similar to those of Karlowsky et al . () who investigated the inheritance of MHR in the UMWO12‐01 and UMWO12‐03 Canadian A. fatua populations. They reported that separate single dominant or semi‐dominant nuclear genes conferred resistance to imazamethabenz, flamprop‐M‐methyl and fenoxaprop‐P‐ethyl in both populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation